Additive increase adaptive decrease congestion control: a mathematical model and its experimental validation - L.A. Grieco; S. Mascolo; R. Ferorelli (Proceedings ISCC 2002 Seventh International Symposium on Computers and Communications, 2002)
Due to the fundamental end-to-end design principle of the TCP/IP for which the network cannot supply any explicit feedback, today the TCP congestion control algorithm implements an additive increase multiplicative decrease (AIMD) algorithm. It is widely recognized that the AIMD mechanism is at the core of the stability of end-to-end congestion control. In this paper we describe a new mechanism we call additive increase adaptive decrease (AIAD). The key concept of the adaptive decrease mechanism is to adapt congestion window reductions to the bandwidth available at the time the congestion is experienced. We propose Westwood++ TCP as an implementation of the AIAD paradigm, and we consider Reno TCP as an example of the AIMD mechanism for comparison. We derive a mathematical model of the throughput of the AIAD mechanism that shows that Westwood++ is stable, is friendly to Reno and increases the fairness in bandwidth utilization. To confirm the validity of the theoretical model Internet measurements are reported.
Keywords: Programmable control; Adaptive control; Mathematical model; TCPIP; Bandwidth; Algorithm design and analysis; Feedback; Stability; Throughput; Internet